Survival analysis of COVID-19 patients with comorbidities in Bekasi during 2020-2021 - Siti Rapingah Rapingah; Seni Wati Ruddin; Shinta Silaswati Silaswati (Universitas 'Aisyiyah Yogyakarta, 2022)
Coronavirus disease 2019 (COVID-19) is a respiratory infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). COVID-19 in patients with comorbidities progresses more rapidly to severity and frequently leads to death. Therefore, the objective of this study is to determine the length of survival and estimation of the Hazard Ratio (HR) of COVID-19 patients with comorbidities. The study design used a retrospective cohort of 3,751 samples and was analyzed using Kaplan Meier and cox regression. The survival function description shows the difference in the mean survival of COVID-19 patients without comorbid and patients with comorbidities of 78 days and 23 days, respectively, with HR of 4.4. In conclusion, comorbid COVID-19 patients possess a lower survival and a higher risk of death.